2004
DOI: 10.1520/jfs2004041
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Sibship Determination Using the ABI Identifiler Multiplex System

Abstract: Fifty known siblings and fifty unrelated pairs were genotyped using the ABI Identifiler STR system and sibship indices computed for each pair. Combined sibship indices (CSIs) for the known siblings ranged from less than 10 to greater than 1 billion. CSIs for the unrelated pairs ranged from 4.5 × 10 −8 to 0.12. In the known sibling group the percentage of loci where both alleles matched was approximately 40%, while the percentage of loci where neither matched was approximately 10%. In the non-sibling group, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 5 publications
2
21
2
Order By: Relevance
“…A CSI less than 1 implies that the two individuals are not related as siblings, while a value over 1 supports this kind of relationship [6]. The difference to our results might be due to the rather low number of individuals investigated by Reid et al [8]. Pu and Linacre, for example, generated 357,630 full sibling pairs from DNA profiles of random populations (Chinese, Caucasian, and African Americans) using the 15 STRs provided with the Identifiler Kit (Applied Biosystems) [9].…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…A CSI less than 1 implies that the two individuals are not related as siblings, while a value over 1 supports this kind of relationship [6]. The difference to our results might be due to the rather low number of individuals investigated by Reid et al [8]. Pu and Linacre, for example, generated 357,630 full sibling pairs from DNA profiles of random populations (Chinese, Caucasian, and African Americans) using the 15 STRs provided with the Identifiler Kit (Applied Biosystems) [9].…”
Section: Resultscontrasting
confidence: 81%
“…However, we did find twins with LRs>1/9 (W-value <10 %) (1.8 % of pairs). This contradicts other studies, e.g., the investigation of 50 known siblings using 15 STR markers by Reid et al [8] in which all sibling pairs had a combined sibship index (CSI) of >10 7 . The CSI is based upon the degree of sharing alleles between two DNA profiles.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…However no such polarization was noted for single allele sharing where the percentage sharing for siblings and non-siblings was 59.19% and 52.52%, respectively. Tzeng et al 4 and Reid et al 9 have also reported this phenomenon. The extreme polarization observed in the degree of zero and 2 allele (s) sharing across various loci in sibling and non-sibling groups indicates that these loci maximize the relative probability of allele sharing by decent versus allele sharing by chance.…”
Section: Log Csi Valuementioning
confidence: 79%
“…Tzeng et al 4 using 15 loci STR panel established a presumptive cutting point of CSI at P3.0 for sibship determination. For Reid et al 9 while testing ABI Identifiler multiplex system (15 STR loci) the likelihood ratio of probable relationship for the non-sibling pairs did not increase above the prescribed threshold value of 1. Thus no consensus is possible on what CSI cut-off point should be used to discriminate siblings from nonrelated individuals.…”
Section: Discussionmentioning
confidence: 94%